Polymeric nanocomposite multifunctional core-shell membrane for periodontal repair and regeneration applications. (December 2022) - Rahmati, Saba; Labbaf, Sheyda; Yaghini, Jaber; Talebi, Alireza
Abstract: Periodontal inflammation injuries affect more than 50% of adults in the society and if left untreated it can result in tooth loss. Here, core-shell nano-fibrous membrane of polycaprolactone/gelatin core and poly (vinyl alcohol)/polyvinylidene fluoride shell is fabricated through electrospining. To facilitate tissue regeneration, bioactive glass nanoparticle (BG) is incorporated within the core and the effect of concentration (10, 25 and 50 wt%) on physical, mechanical and biological properties is thoroughly studied. The diameter of the fibrous structures was 270 ± 25 nm to 510 ± 39 nm. The tensile strength was greatly influenced by the addition of BG such that ultimate tensile stress increased from 2.7 MPa to 3.4 MPa in 0 and 10 wt% BG containing group, respectively. By investigating the piezoelectricity of the membranes, core-shell sample with 25% BG showed the highest output voltage of 39 ± 4 kV m −3 . The core-shell sample with 25% BG sample was shown great hemocompatibility with a low hemolysis ratio of 0.5% and platelets attachment test confirmed that the attached platelets were not activated and aggregated or pseudopodium. Drug loaded membrane revealed an antibacterial activity against Staphylococcus aureus bacteria. The cell proliferation was positively influenced by the presence of BG, further confirming the suitability of the resultant structure for periodontal applications. Graphical abstract: Image 1 Highlights: Fabrication of nano-fibrous PCL/gelatin core and poly (vinyl alcohol)/polyvinylidene fluoride shell. Bioactive glass nanoparticle successfully incorporated within the core-shell structure. Electro-simulating polymeric membrane showed a great piezoelectric coefficient of 7.9 ± 0.7 pC/N and output voltage of 39 ± 4 kV m −3 . Durable and flexible membrane with 6.4 MPa ultimate tensile stress, 541 KPa tensile modulus and 69% elongation rate. Membrane supports the proliferation and adhesion of the cells with admirable blood compatibility and cell response. Optimized structure can support both hard and soft tissue in periodontal application.